Bifunctional W/NH Cuboidal Aminophosphino W3S4 Cluster Hydrides: The Puzzling Behaviour behind the Hydridic‐Protonic Interplay. Issue 42 (11th October 2021) - Guillamón, Eva; Beltrán, Tomás F.; Safont, Vicent S.; Castillo, Carmen E.; Algarra, Andrés G.; Fernández‐Trujillo, M. Jesús; Pedrajas, Elena; Pino‐Chamorro, José Angel; Basallote, Manuel G.; Llusar, Rosa
Abstract: The novel [W3 S4 H3 (edpp)3 ] + (edpp=(2‐aminoethyl)diphenylphosphine) (1 + ) cluster hydride with an acidic −NH2 functionality has been synthetized and studied. Its crystal structure shows the characteristic incomplete W3 S4 cubane core with the outer positions occupied by the P and N atoms of the edpp ligands. Although no signal due to the hydride ligands is observed in the 1 H NMR spectrum, hydride assignment is supported by 1 H‐ 15 N HSQC techniques, the changes in the 31 P{ 1 H} NMR chemical shift, and FT‐IR spectra in the W−H region of the deuterated [W3 S4 D2 H(edpp)3 ] + (1 + ‐d2 ) samples. Moreover, all NMR evidences suggest that one of the hydrogen atoms of the NH2 group in 1 + is rapidly exchanging with the hydride. The reaction of 1 + with acids (HCl, HBr and DCl) features complex polyphasic kinetics with zero‐order dependence with respect to the acid concentration, being also independent of the solvent nature. This behavior differs from that of their diphosphino analogues, suggesting a different mechanism. Abstract : A novel [W3 S4 H3 (edpp)3 ] + cluster hydride with an acidic −NH2 functionality has been prepared and characterized. NMR studies evidence a rapid exchange between the hydride and one of the hydrogen atoms of the NH2 group. The cluster reacts with HX acids to afford the corresponding substitution product with a zero‐order kinetics with respect to the acid concentration and independent of the solvent nature.